What Kind of Place is this? - Tristan Bruslé (South Asia Multidisciplinary Academic Journal)
The lives of nearly one million migrants in Qatar are in a ‘state of exception’ (Agamben). Distanced from mainstream society, they live in labour camps situated in desolate areas. In a space designed to render low qualified migrants invisible, Nepalese people are among those who try to make theirs a temporary place. Spatial strategies of appropriation, from the camp to the bed in the room, are nevertheless limited by the structures of domination that migrants live in. Through the study of the everyday routine and spatial practices, I show that the camp does indeed bear ambivalent values, associated with jail, with village-like feelings or with the achievements made possible by migration.